Kecemasan pada pengguna media sosial Twitter: Benarkah menyebabkan self-injury? - Putri Zalfa Salsabila; Herlan Pratikto; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract The purpose of this study was to determine the relationship between self-injury and anxiety among Twitter social media users. This research is included in correlational research. The sample of this research is 100 samples. The sampling technique used was purposive sampling. Retrieval of data using a self-injury scale and anxiety scale. The data analysis process uses the Product Moment correlation which shows a significant correlation between anxiety and self-injury in Twitter users. this proves that the hypothesis proposed by the researcher is accepted. Keywords: self injury, anxiety, Twitter social media users Abstrak [Left, Arial 11, Bold, Italic] Tujuan penelitian ini adalah untuk mengetahui hubungan kecenderungan self injury dengan kecemasan pada pengguna media social Twitter. Penilitian ini termasuk dalam penelitian korelasional. Sampel penelitian ini sebanyak 100 sampel. Teknik Sampling yang digunakan adalah purposive sampling. Pengambilan data menggunakan skala self injury dan skala kecemasan. Proses analisis data menggunakan korelasi Product Moment yang menunjukkan adanya korelasi yang signifikan antara kecemasan dan self injury pada pengguna twitter. hal ini membuktikan bahwa hipotesis yang diajukan oleh peneliti oleh diterima. Kata kunci: self injury, kecemasan, pengguna social media Twitter